f(

g(b) -> c

b -> c

R

↳Dependency Pair Analysis

F(X, g(X),Y) -> F(Y,Y,Y)

Furthermore,

R

↳DPs

→DP Problem 1

↳Forward Instantiation Transformation

**F( X, g(X), Y) -> F(Y, Y, Y)**

f(X, g(X),Y) -> f(Y,Y,Y)

g(b) -> c

b -> c

On this DP problem, a Forward Instantiation SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

F(X, g(X),Y) -> F(Y,Y,Y)

F(X, g(X), g(X''')) -> F(g(X'''), g(X'''), g(X'''))

The transformation is resulting in one new DP problem:

R

↳DPs

→DP Problem 1

↳FwdInst

→DP Problem 2

↳Remaining Obligation(s)

The following remains to be proven:

**F( X, g(X), g(X''')) -> F(g(X'''), g(X'''), g(X'''))**

f(X, g(X),Y) -> f(Y,Y,Y)

g(b) -> c

b -> c

Duration:

0:00 minutes